Dampak Impor Beras Terhadap Harga Eceran Tertinggi Beras Lokal Indonesia - Muhammad Kahlil Gibran Umar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rice is a major food commodity in Indonesia that plays an important role in economic stability and people's lives. However, the increasing demand for domestic rice often forces the government to implement import policies to maintain availability. This study aims to analyze the impact of rice imports on the highest retail price (HET) of local rice in Indonesia, using a descriptive qualitative approach. The study includes in- depth interviews with farmers, traders, and consumers, as well as analyzing the related socio-economic context. The results show that rice imports have a significant impact on local rice prices. On the one hand, increased supply due to imports can lower retail prices, benefiting consumers in the short term. However, on the other hand, it hurts local farmers as their rice selling prices become uncompetitive. The price instability caused by import policies also affects farmers' motivation to increase production. This study highlights the importance of a balanced import policy management, taking into account the protection of local farmers through subsidy support or technical assistance, while meeting consumer needs. With a holistic approach, the government is expected to maintain price stability and sustainability of the national agricultural sector.